2013
DOI: 10.3390/toxins5112258
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ATP Citrate Lyase and Acetyl CoA Levels with Trichothecene Production in Fusarium graminearum

Abstract: Thecorrelation of ATP citrate lyase (ACL) and acetyl CoA levels with trichothecene production in Fusarium graminearum was investigated using an inhibitor (precocene II) and an enhancer (cobalt chloride) of trichothecene production by changing carbon sources in liquid medium. When precocene II (30 µM) was added to inhibit trichothecene production in a trichothecene high-production medium containing sucrose, ACL expression was reduced and ACL mRNA level as well as acetyl CoA amount in the fungal cells were reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…Therefore, it seemed that the supply of additional acetyl-CoA to the mevalonate pathway may be a key event for initiating trichothecene production. 68) We quantified the amount of acetyl-CoA in fungal cells cultured with or without precocene II and/or sucrose. Precocene II reduced the amount of acetyl-CoA to the level observed in cells cultured without sucrose, in which trichothecene was not produced.…”
Section: Mode Of Action Of Precocene IImentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it seemed that the supply of additional acetyl-CoA to the mevalonate pathway may be a key event for initiating trichothecene production. 68) We quantified the amount of acetyl-CoA in fungal cells cultured with or without precocene II and/or sucrose. Precocene II reduced the amount of acetyl-CoA to the level observed in cells cultured without sucrose, in which trichothecene was not produced.…”
Section: Mode Of Action Of Precocene IImentioning
confidence: 99%
“…Precocene II reduced the amount of acetyl-CoA to the level observed in cells cultured without sucrose, in which trichothecene was not produced. 68) By the proteome analysis with twodimensional differential gel electrophoresis, it was found that expression of ATP citrate lyase (ATPCL) in the presence of sucrose was significantly reduced by precocene II. 68) ATPCL is a key enzyme to produce acetyl-CoA in the fungal cytosol.…”
Section: Mode Of Action Of Precocene IImentioning
confidence: 99%
See 2 more Smart Citations
“…Acetyl-CoA, which acts as a starter unit for many secondary metabolites, including polyketides, alkaloids, β lactam antibiotics, etc., can originate from mitochondria and peroxisomes through β-oxidation of lipids (Maggio-Hall et al, 2005). In F. graminearum, the cytosolic acetyl-CoA pool, generated by the action of ATP-citrate lyase, plays an important role in the production of DON (Son et al, 2011;Sakamoto et al, 2013). In addition to acetyl-CoA, other forms of acyl-CoAs also serve as starter units for the biosynthesis of various secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%